Providing A Model for Supply Chain Agility of Ground-Based Military Products and Its Impact on Supply Chain Performance - Akbar Rahimi; Abbas Raad; Akbar Alamtabriz; Alireza Motameni (International Journal of Industrial Engineering and Production Research, 2019)
Nowadays, Military products of superpowers countries have a high level of diversity, delivery speed, and appropriative operational functionality. Therefore, Production of varied, high quality and high speed delivery military products, is essential for enhance Iranchr('39')s defensive deterrence power. Defense industries supply chain agility is an answer to how to produce military products with these features. This paper, with the aim of providing supply chain agility model in defense industries, first, identifies the most important supply chain agility practices, Then, using factor analysis, categorizes the practices and validates them based on structural equation modeling (SEM) and finally, using Interpretative Structural Modeling (ISM), presents a model that shows the relationships and hierarchy between these practices. The results show that out of a total of 62 practices introduced in the previous research for agile supply chain, 41 practices in the agility of the supply chain of defense industries are effective. These practices were classified in 8 categories include supplier relationship, workshop level management, organizational structure improvement, human resource management, product designing, improve and integrate the process, application of information technology, and customer relationship. Improvement of organizational structure was at the lowest level of the model. Therefore, managers first should focus on it.